Osseointegration assessment of chairside argon-based nonthermal plasma-treated Ca-P coated dental implants - Giro, Gabriela [UNESP]; Tovar, Nick; Witek, Lukasz; Marin, Charles; Silva, Nelson R.F.; Bonfante, Estevam A.; Coelho, Paulo G. (Wiley, 2013)
This study investigated the effect of an Argon-based nonthermal plasma (NTP) surface treatment-operated chairside at atmospheric pressure conditions applied immediately prior to dental implant placement in a canine model. Surfaces investigated comprised: Calcium-Phosphate (CaP) and CaP + NTP (CaP-Plasma). Surface energy was characterized by the Owens-Wendt-Rabel-Kaelble method and chemistry by X-ray photoelectron spectroscopy (XPS). Six adult beagles dogs received 2 plateau-root form implants (n = 1 each surface) in each radii, providing implants that remained 1 and 3 weeks in vivo. Histometric parameters assessed were bone-to-implant contact (BIC) and bone area fraction occupancy (BAFO). Statistical analysis was performed by Kruskall-Wallis (95% level of significance) and Dunn's post-hoc test. The XPS analysis showed peaks of Ca, C, O, and P for the CaP and CaP-Plasma surfaces. Both surfaces presented carbon primarily as hydro-carbon (CAC, CAH) with lower levels of oxidized carbon forms. The CaP surface presented atomic percent values of 38, 42, 11, and 7 for C, O, Ca, and P, respectively, and the CaPPlasma presented increases in O, Ca, and P atomic percent levels at 53, 12, and 13, respectively, in addition to a decrease in C content at 18 atomic percent. At 1 week no difference was found in histometric parameters between groups. At 3 weeks significantly higher BIC and BAFO were observed for CaPPlasma treated surfaces. Surface elemental chemistry was modified by the Ar-based NTP. Ar-based NTP improved bone formation around plateau-root form implants at 3 weeks compared with CaP treatment alone. © 2012 Wiley Periodicals, Inc.
Keywords: Argon plasma; Implant surface treatment; In vivo; Modified surface; Osseointegration; Argon plasmas; Implant surface; In-vivo; Modified surfaces; Atmospheric pressure; Atoms; Bone; Calcium; Carbon; Dental prostheses; Photoelectrons; Plasmas; Surface treatment; X ray photoelectron spectroscopy; Argon; argon; calcium phosphate; hydrocarbon; atmospheric pressure; bone regeneration; dog; histometry; in vivo study; musculoskeletal system parameters; nonhuman; plasma gas; tooth implant; Animals; Calcium Phosphates; Coated Materials, Biocompatible; Dental Implants; Dogs; Implants, Experimental; Male; Microscopy, Electron, Scanning; Osteogenesis; Plasma Gases